FEMINISM REFLECTION THROUGH FAMILY COMMUNICATION IN THE MAIN CHARACTER OF LITTLE WOMEN MOVIE - yanti rosalinah; Ibnu Subroto; Rina Lestari (Lembaga Penelitian & Pengabdian Masyarakat Universitas Bina Sarana Informatika, 2022)
This paper is meant to understand how Jo march, who is the female lead character, is portrayed and how the film reflects feminist values through the character of Jo march. The analysis in this text uses a feminist approach because the purpose of this writing is to find the feminism of the main character and how communication in the family affects all the decisions taken by the main character in this film. This analysis is based on the sources of Little Women movie by Greta Gerwig. The method of analysis used is a qualitative descriptive method. To find the feminism values of the Jo March character, there are three problem formulated in this paper. The first problem is knowing the type of feminism shown by the main character, Jo March. Second, how is the point of view of women shown in the Little Women movie. And last how does communication with family affect the feminism side of the main character.. Analysis showed that: (1) in the film little women, the main character featured two types of feminism, which is liberal feminism and Marxist feminism. (2) The point of view toward women, which women at that time were limited by the thought that they should marry in order to have a good life. (3) Finally, Family has a very important role to build a person's mindset.